2019
DOI: 10.3390/ijerph16203904
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an 8-Week Exercise and Sport Intervention on Post-Traumatic Stress Disorder Symptoms, Mental Health, and Physical Fitness among Male Refugees Living in a Greek Refugee Camp

Abstract: Objective: To explore the potential impact of exercise and sport training on symptoms of post-traumatic stress disorder (PTSD), depression, anxiety, quality of life, pain, and fitness in male refugees living in a Greek refugee camp. Methods: This investigation was designed as a one group pre-test/post-test study. A total of 45 refugees (Mage = 25.6) participated in the data assessment. All participants were invited to engage in an 8-week exercise and sport intervention. Data were analysed with hierarchical reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…In our study, the exercise and sport program consisted of 32 training sessions across an 8-week period. As reported previously [21], the mean participation rate across our sample was 7.5 training sessions (SD = 6.5). However, participation varied greatly, with a range of 0 to 23 attended sessions.…”
Section: Acceptability and Perceived Benefitssupporting
confidence: 67%
See 1 more Smart Citation
“…In our study, the exercise and sport program consisted of 32 training sessions across an 8-week period. As reported previously [21], the mean participation rate across our sample was 7.5 training sessions (SD = 6.5). However, participation varied greatly, with a range of 0 to 23 attended sessions.…”
Section: Acceptability and Perceived Benefitssupporting
confidence: 67%
“…In a recent one-group pre-test/post-test study with 38 male refugees living in a Greek refugee camp, our research group showed that regular participation in an 8-week sport and exercise program has the potential to positively impact on a variety of mental health outcomes, including post-traumatic stress symptoms, depressive symptoms, anxiety symptoms, health-related quality of life, perceived fitness, handgrip strength, and cardiorespiratory fitness [21]. Refugees who participated more often in the exercise program had more favorable scores at post-intervention, after controlling for baseline and potential confounders.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research has shown various protective factors for anxiety, such as self-efficacy ( 13 ), coping style ( 14 ), and social support ( 15 ). A positive role for physical activity in the prevention of anxiety has also been shown in several types of recent studies ( 16 18 ). Physical fitness can be defined as the capacity to perform physical activity ( 19 ), and physical fitness is more predictive of health outcomes than is physical activity in children ( 20 ).…”
Section: Introductionmentioning
confidence: 59%
“…Saharan Africa (SSA, 59.4%) and with an increasing percentage of fertile females [22][23][24][25][26]. Further, the incidence of BMD loss and related fractures attributed to a specific eating pattern has also been targeted for guidelines and suggestions within the EU/EEA [8].…”
Section: Plos Onementioning
confidence: 99%
“…CD4+ T-cell count and plasma HIV-RNA levels were assessed as previously reported [9]. 25-hydroxy-vitamin D (25(OH)D) was assayed as previously reported [21,22,25]. We considered a serum 25(OH)D concentration of 30 ng/mL as a threshold value for identifying low levels of vitamin D, as previously reported (standard value of our laboratory: 30-80 ng/mL) [13].…”
Section: Plos Onementioning
confidence: 99%